Integrating the technology acceptance model for social media-based learning with authentic leadership development: symmetric and asymmetric modeling - Asghar, Muhammad Zaheer; Rasool, Samma Faiz; Seitamaa-Hakkarainen, Pirita; Arif, Seema; Bano, Sumaira (Frontiers in Psychology, 2023)
Introduction The growing trend of social media use has influenced all segments of society, including education, during the COVID-19 pandemic. At the same time, authentic leadership is an emerging concept in positive psychology for dealing with emergencies in the digital era. The possibility of a relationship between the two was checked in preservice teachers studying in a teacher education department of a university in Pakistan. The conceptual framework of the study was built around teaching acceptance model (TAM) and Authentic leadership theory. Methods The survey method suited the aim of the research, and questionnaires aided us in gathering participant self-reporting responses. We conducted two surveys, and in between them, a course was taught online using social media as a teaching and learning platform. The survey results checked preservice teachers’ positive intentions toward social media-based learning, and the post-course survey studied the development of Authentic leadership attributes among the preservice teachers. Technology acceptance was measured across three constructs: ease of use, usefulness, and positive intentions. The results also reported the development of three authentic leadership characteristics: ethics, self-regulation, and self-awareness. Results and discussion This study is among the pioneering studies integrating TAM (i.e., the acceptance of social media-based learning) with leadership theory (i.e., authentic leadership). It also adds a methodological contribution by combining symmetrical (i.e., partial least squares structural equation modeling) and asymmetrical (i.e., fuzzy set qualitative comparative technique) for data analysis. The study’s findings are valuable for teacher education institutions, as they help prepare future teachers to become authentic leaders capable of addressing future crises by leveraging education through social media-based teaching and learning platforms.